Unpacking the Complexities of Re-Enrollment in Secondary Schools: A Dual Perspective from Parents and Teenage Mothers in Osun State, Nigeria - Iwintolu, Rukayat; Olagunju, Barakat; Jekayinoluwa, Jacob; Adeniji, Ajibola; Alao, Kayode; Adegoke, Toluwalope (International Journal of Educational Review, 2024)
Teenage pregnancy is a multifaceted issue that intersects with various social, cultural, and economic factors. The issue of teenage pregnancy raises important questions about the well-being and future prospects of young girls and most importantly, efforts at reschooling them. This study adopted a qualitative method using interview method to explore both teenage mothers’ and their parents willing to reenroll their daughters in school. The population for this study consisted pregnant girls awaiting child bearing, young-mothers and teenage mothers who had dropped out of school or still attending school. Eight teenage mothers that dropped out of school and two parents were reached and interviewed. The results revealed that teenage mothers admitted that they missed school, and interested in continuing their education. Parents were worried about their daughters dropping out of school and were willing to help them complete their secondary school education, while identifying financial difficulties as a major challenge.